Tinjauan Literatur Sistematis Lean Six Sigma Metode 5S di Sektor Pergudangan - Isnanto, Septian Ade; Larutama, Wiku (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This systematic literature review explores Lean Six Sigma (LSS) with a focus on the 5S methodology in the warehousing sector. The warehousing sector frequently encounters challenges such as disorganized layouts, prolonged search times, inefficient space utilization, and safety risks. This study aims to analyze 5S implementation, identify its challenges and benefits, and explain its integration within the LSS framework. Employing a systematic literature review (SLR) of 10 articles published from 2021-2024, the research synthesizes findings across diverse industries. Key results indicate that 5S significantly improves operational efficiency, reduces search times, optimizes space, and enhances safety. While 5S fosters a positive organizational culture, challenges include employee resistance and sustaining discipline. The review concludes that 5S is a fundamental and effective strategy for holistic warehouse performance improvement within the LSS framework